Antifertility effects of mifepristone and epostane alone and in combination in rats - Liu Chang-Guan; Lin Zhong-Ming; Li Wei-Kang; Wu Xiao-Yun; Wang Zhong-Xing; Xue Tao; Xu Rui-Ying (Acta Pharmacologica Sinica, 2016)
A complete interceptive action on pregnancy was shown after ig mifepristone (RU-486) 16 mg.kg-1 or epostane 96 mg.kg-1 on d 10 of pregnancy in rats. The ig ED50 (95% fiducial limits) of RU-486 when given alone and in combination with epostane 12 mg.kg-1 were found to be 7.8 (5.3-10.0) and 2.6 (2.0-3.3) mg.kg-1, respectively (P < 0.05), while those of epostane when given alone and in combination with RU-486 4 mg.kg-1 were 25.5 (19.4-33.6) and 5.6 (4.7-7.4) mg.kg-1, respectively (P < 0.05). An absorption promotor, sodium dodecyl sulfate 24 mg.kg-1 ig, when given in combination with RU-486 8 mg.kg-1 or epostane 24 mg.kg-1, induced complete interceptive action on pregnancy. Levels of plasma progesterone declined significantly when epostane 12 mg.kg-1 was given in combination with RU-486 4 mg.kg-1 as compared with epostane 12 mg.kg-1 alone (P